2015
DOI: 10.3390/ijerph120201849
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Effects of Physical Inactivity and Obesity on Gait Speed in Older Adults with Frequent Knee Pain: Data from the Osteoarthritis Initiative

Abstract: Physical inactivity (PI) and obesity are risk factors for many health conditions, including knee pain (KP). The purpose of the present study was to examine the 6-year effects of PI and obesity on gait speed (GS) among older adults with frequent KP. This prospective cohort study used data from the Osteoarthritis Initiative (OAI). At baseline, we studied 1788 adults aged 45 to 79 years old. We grouped the participants into four categories according to baseline scores on the Physical Activity Scale for the Elderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
3
9
0
2
Order By: Relevance
“…A directed acyclic graph approach 27 was used to determine which variables would be appropriate to use to adjust for the effects of true aerobic capacity and aid in isolating the distorting effect of motor function on the aerobic capacity measures. Based on the literature, we identified the following potential common causes of both motor dysfunction (lower CGS) and lower aerobic capacity measurement: greater stroke severity, 20,28-30 increased age, 3,31 female sex, 3,31 higher BMI, 3,32,33 depression 34,35 and lower physical activity history. 1,3,20 Hypothesized causal relationships were graphed with unidirectional arrows (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…A directed acyclic graph approach 27 was used to determine which variables would be appropriate to use to adjust for the effects of true aerobic capacity and aid in isolating the distorting effect of motor function on the aerobic capacity measures. Based on the literature, we identified the following potential common causes of both motor dysfunction (lower CGS) and lower aerobic capacity measurement: greater stroke severity, 20,28-30 increased age, 3,31 female sex, 3,31 higher BMI, 3,32,33 depression 34,35 and lower physical activity history. 1,3,20 Hypothesized causal relationships were graphed with unidirectional arrows (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Knee osteoarthritis (OA) is a chronic disease that manifests as pain, stiffness, swelling and muscle weakness [ 1 , 2 ], causes functional impairment due to lower limb muscle weakness, and is one of the most common diseases in the older persons [ 3 7 ]. A previous study reported that subjects with knee pain had a significantly higher incidence of quadriceps weakness after a 30-month period than subjects without pain and that patients with knee OA had a 76% reduction in eccentric quadriceps strength than healthy subjects [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are similar to those of previous studies that have demonstrated independent associations between KP, obesity, and GS. 33 35 White et al conducted a multicenter OA cohort study and found that obesity has an important association with slow GS independent of KP. 33 In a cross-sectional study, Vincent et al found an association between KP, obesity, and fear of movement.…”
Section: Discussionmentioning
confidence: 99%